Biofuels Economy, Environment and Sustainability - Fang, Zhen (IntechOpen, 2013)
This book overviews social, economic, environmental and sustainable issues by the use of biofuels written by professionals. It should be of interest for students, researchers, scientists and technologists in biofuels.